Identification of a novel WNK1–ROS1 fusion in a lung adenocarcinoma sensitive to crizotinib. (March 2019) - Liu, Yutao; Liu, Tianfeng; Li, Nan; Wang, Tao; Pu, Yue; Lin, Rui
Highlights: A novel WNK1–ROS1 fusion has been identified in a lung adenocarcinoma. The patient harboring WNK1–ROS1 fusion was sensitive to crizotinib treatment. The patient developed ROS1 G2032R mutation when disease progressed. The WNK1–ROS1 rearrangement appears to be a novel driver of the lung adenocarcinoma. Abstract: Objectives: Non-small-cell lung cancer (NSCLC) has various driver mechanisms, including ROS1 rearrangement with different fusion patterns. There is a need to identify and evaluate new ROS1 fusions and the response to targeted therapy. Materials and methods: A targeted next-generation sequencing (NGS) panel was used to analyze DNA extracted from tumor tissue and blood samples from an NSCLC patient. Results were validated using Sanger sequencing. Results: We found a novel ROS1 rearrangement form, namely a WNK1–ROS1 fusion. The transmembrane and kinase domains of ROS1 remained intact in this fusion. No EGFR, MET, KRAS, ALK, ROS1 or other NSCLC driver mutations were detected in the patient. The patient achieved a partial response after treatment with crizotinib. When disease progressed, ROS1 G2032R mutation—a classical mechanism of crizotinib resistance—was detected in the DNA sample extracted from the patient's plasma sample. Conclusion: We identified a novel WNK1–ROS1 fusion that was sensitive to crizotinib and developed an ROS1 G2032R mutation when the disease progressed. The WNK1–ROS1 rearrangement appeared to be a novel driver of the lung cancer.